Networking Social Scholarship…Again - Martin, Shawn (KULA)

(untitled) (University of Victoria Libraries, 2019)
This paper proposes to answer several questions that arise from the actions of American scientists between 1840 and 1890. How did the broader organization of science in the late nineteenth century create a system of professional disciplines? Why did the American Association for the Advancement of Science (AAAS) form, and why did specialized societies like the American Chemical Society (ACS) later found an organization separate from the AAAS? Why did these professional societies create journals, and how did these journals help to communicate science? This paper combines both quantitative textual analysis and qualitative historical and sociological methods within the context of nineteenth-century American science. It is hoped that by broadening the methods used, and by better understanding the early deliberations of scientists before there was a formal scholarly communication system, it may be possible to contextualize current debates about the need for changes in the scholarly communication system.